Doktrin Roh Jahat: Dalam Perspektif Iman Kristen - Aliadi, Frans; Sukarna, Timotius (JURNAL KADESI, 2025)
This article discusses the doctrine of evil spirits from a Christian faith perspective, focusing on the existence and activities of supernatural beings that oppose the will of God. In Christian theology, evil spirits are associated with sin, temptation, and human suffering, and are considered a serious spiritual threat. Although the concept of evil spirits is often overlooked in the modern era, many people still experience negative spiritual phenomena, highlighting the importance of this topic. A lack of deep understanding of the doctrine of evil spirits can leave Christians vulnerable to spiritual attacks. This article aims to deepen theological understanding of the existence and role of evil spirits and to provide insights on how Christians can spiritually confront these negative influences. The research also emphasizes the relevance of this doctrine in daily life and spiritual practice, referencing the Bible, especially the New Testament, where Jesus Christ is depicted as having the authority to cast out evil spirits.